Produção de invertases a partir de microrganismos isolados de frutos amazônicos - Bastos, Lunara Thaís Alves de (Universidade Federal do Tocantins, 2022)
The Brazilian plant diversity is rich in species that are not commercially explored, among them the Amazonian fruits, which are nutritious and abundant in bioactives. The peach palm and tucumã are easily found in the Amazon region and can be sources of microorganisms that produce invertase, a hydrolase capable of cleaving sucrose into glucose and fructose, resulting in a sweeter compound than sucrose. And fructosyltransferase, which transfers fructosyl groups to a sucrose molecule or to a fructooligosaccharide. The objective of this work was to isolate microorganisms that produce invertase and fructosyltransferase from peach palm and tucumã fruits, in addition to analyzing different cultivation conditions and characterizing the biochemical properties of the synthesized enzymes produced. Among 481 strains isolated from the fruits, 19 showed enzyme production and, then, were analyzed for morphological and biochemical characteristics. However, the PP6 strain, Bacillus sp. isolated from peach palm, showed more promising results in terms of enzyme synthesis and production, being subjected to several analyzes referring to different carbon sources (glucose, fructose, xylose, sucrose, lactose, galactose, inulin, starch, pectin, glycerol, sorbitol and inositol) and nitrogen (yeast extract, tryptone, peptone, corncine, ammonium sulfate, ammonium phosphate and ammonium chloride), as well as the biochemical characterization in which the influence of pH (1.0 - 8.0) and temperature were evaluated. (20-70°C) of the reaction medium in the enzymatic activity as well as the biochemical characterization, in which the optimal pH and temperature, maximum stability time, thermal stability (35 - 60 °C) were evaluated. and compared to incubation pH (1.0 - 8.0) what is the pH range?), in addition to studies of different culture conditions (addition of adjuvants, sucrose concentration and pH of the culture medium) . The best syntheses of invertase/fructosyltransferase production were found using sucrose (1.92 U /mL/0.89 U /mL) and ammonium sulfate (2.01 U /mL/0.78 U/mL) as carbon and nitrogen sources, respectively. The highest activity values for invertase (1.96 U/mL) were reached at pH 4.5, while for fructosyltransferase (0.78 U/mL) they were obtained at pH 3.5. However, both enzymes exhibited higher activity values at 50 ºC. The optimal pH of invertase was observed at 4.0 while fructosyltransferase was pH 3.5, however both had their highest performance at 50°C. The results obtained in this work will contribute to the generation of information about the microbial community of the analyzed fruits, adding knowledge to the area of bioprocesses, valuing and increasing the knowledge around the rich Amazon biome, in addition to presenting a new source of invertase and fructosyltransferase enzymes for the industrial application.